2017
DOI: 10.1080/17538068.2017.1313479
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric residents’ attitudes and practice patterns regarding transition to adult-oriented care

Abstract: Background: Most youth with chronic illness will survive into adulthood. The complexity of the medical history and care in these patients necessitates a well-planned and coordinated transition over several years as they move from pediatric to adult-oriented health care. Methods: We assessed pediatric residents’ practice patterns and attitudes regarding transition communication by administering a survey about transition to pediatric, combined internal medicine-pediatrics, pediatric neurology, and combined psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Guidelines recommend starting a conversation about transition when a patient is 12 to 14 years old. 1,3 Many pediatricians feel that is too early, [4][5][6] but as shown in the interview, connecting to services is time-consuming. Starting a transition conversation early allows families to consider and plan for a health care transition as well as transitions in other life domains.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines recommend starting a conversation about transition when a patient is 12 to 14 years old. 1,3 Many pediatricians feel that is too early, [4][5][6] but as shown in the interview, connecting to services is time-consuming. Starting a transition conversation early allows families to consider and plan for a health care transition as well as transitions in other life domains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys have focused on transition practices with minimal exploration of educational preferences. 6,7 We plan to incorporate preferences identified in this work into educational endeavors in our health system to optimize provider engagement.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, research focusing on providers has demonstrated that pediatric and adult providers, including residents and attendings, do not follow transition guidelines. 6,7 To improve transition, professional organizations have recommended increased education for providers during training and Continuing Medical Education (CME). 1 Given these recommendations, we sought to devise an educational intervention within a pediatric health system to improve knowledge of best practices around transition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transition process is frequently turbulent and experienced negatively by CYP, their families and caregivers 20 . Obstacles to successfully implementing transition include funding limitations, lack of continuity and coordination between child and adult services 21 23 and limited training opportunities and specialist expertise in the adult system 24 27 . In addition, there are significant changes to healthcare provider relationship and reduced support levels in the adult environment 28 .…”
Section: Introductionmentioning
confidence: 99%